2006
DOI: 10.1111/j.1468-1331.2006.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cognitive status, MRI‐ and SPECT‐imaging in CADASIL patients

Abstract: Although there is evidence for correlations between disability and magnetic resonance imaging (MRI) total lesion volume in autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), the significance of structural MRI abnormalities for cognitive dysfunction remains controversial. We performed detailed neuropsychological testing, high resolution MRI, and Tc-99m-ethyl cysteinate-dimer SPECT in three CADASIL patients. MR-images were rated independently by two investigators for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Later in the disease, there is likely a critical point at which the extent of damage leads to a drop in CBF and acceleration of the disease process. SPECT studies have shown global hypoperfusion that appeared worse in older and more severely affected subjects [32], but perfusion results were not always clearly related to clinical outcomes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Later in the disease, there is likely a critical point at which the extent of damage leads to a drop in CBF and acceleration of the disease process. SPECT studies have shown global hypoperfusion that appeared worse in older and more severely affected subjects [32], but perfusion results were not always clearly related to clinical outcomes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics factors could be mentioned 20 , but also genetic diversity among individuals from different countries and cohorts 21 22 . The relationship between MRI lesion patterns and cognitive state in patients with CADASIL is still under study 14,[23][24][25][26] . It has been suggested 24,27 that cognitive impairment in CADASIL is related to the accumulation of lacunar infarts and increase in ventricular volume but not to brain atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The cortical uptake ratio in single photon emission computed tomography (SPECT) has been shown to reflect the in vivo perfusion state . The quantitative region‐of‐interest‐based (ROI‐based) information conveyed by factors such as neuronal loss, blood flow and white matter lesions is implied in changes of cerebral perfusion. Although many studies have explored the effects of tHcy in AD using brain magnetic resonance imaging (MRI), there is a paucity of literature regarding the influence of tHcy on cerebral perfusion.…”
Section: Introductionmentioning
confidence: 99%